«Abay» magazine – golden support to national spirituality (Herald of Journalism, 2018)
In this article there is a speech about history and the doctrine of the magazine Abay issued in 1918 in Semey. There is estimated the contribution of the magazine to the Kazakh spirituality. Relatively and connectively explains the similarity of the program «Alash» with the direction of the magazine «Abai»